Rebalancing of exchange traded funds in stock market using option trading strategies - Elegeti, Vinaykumar (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: The finance and academic industries are highly discussed in the stock market trading domain. The increase in economic globalization shows the connection among stock markets in different countries, which produces the effect of risk conduction in the market. Forecasting the direction of every day’s stock market return is important and challenging. The growing complexity and dynamic features in stock markets are difficult in the financial industry. The inflexible trading method developed by financial practitioners utilized a larger amount of stock market features and is failed to achieve a satisfactory result in every condition of the market. Further, the existing data mining approaches are incomplete and inefficient. Aim: To overcome the issues in stock and problem of existing methods, proposed option trading strategies for rebalancing Exchange Traded Fund (ETF) in the stock market. Rebalancing-ETF measure the volatility of the stock to track the error of model and rebalance the threshold quality to improve the trade. The proposed method increases the order of threshold quantity to rebalance the trade. Results: The result showed that the minimum orders increases in rebalancing trade, which reduces the impact of price formations in market. The tracking error occurs when the larger quantity of threshold value reduces the quantity. Then, the markets are changed significantly when the Net Asset Values (NAV) of rebalancing ETF increases.